2022
DOI: 10.1038/s41598-022-24062-3
|View full text |Cite|
|
Sign up to set email alerts
|

Hot spring bathing is associated with a lower prevalence of hypertension among Japanese older adults: a cross-sectional study in Beppu

Abstract: Hot spring bathing is practiced to help manage various diseases, including hypertension. We investigated the preventive effects on hypertension of hot spring bathing among older adults in a data analysis using responses to a previous questionnaire with the aim to identify a novel approach in the prevention and management of hypertension. Among 10,428 adults aged ≥ 65 years, we assessed the hot spring bathing habits of 4001 individuals with a history of hypertension. We calculated odds ratios (OR) with 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To date, only one study has investigated the association between habitual night-time hot spring bathing and a lower prevalence of hypertension (Yamasaki et al 2022). The present study showed, for the rst time, that night-time hot spring bathing decreases both systolic and diastolic blood pressure in the morning, especially systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only one study has investigated the association between habitual night-time hot spring bathing and a lower prevalence of hypertension (Yamasaki et al 2022). The present study showed, for the rst time, that night-time hot spring bathing decreases both systolic and diastolic blood pressure in the morning, especially systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that hypertension (OR 0.397) was independently and signi cantly associated with night-time hot spring bathing. We previously identi ed an inverse relationship between habitual night-time hot spring bathing and a history of hypertension (Yamasaki et al 2022). These results support our hypothesis that habitual night-time hot spring bathing protects against hypertension development and may be suitable for older patients to prevent hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that hot spring bathing is related to a reduced prevalence of hypertension [ 22 ]. In addition, it is known that psychosocial stress leads to the development of hypertension [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have reported that hot spring therapy may benefit sleep quality and quality of life in patients with musculoskeletal and skin diseases 3 5 . Several papers have also reported the effectiveness of bathing in hot springs in alleviating cardiovascular disease and hypertension 6 – 12 . Hot spring use is recommended for medical patients who have particular symptoms, including symptoms of the gastrointestinal tract, respiratory system, ear, nose, throat, or skin; gynecological symptoms; and rheumatological symptoms 13 15 .…”
Section: Introductionmentioning
confidence: 99%